Brain Tumor Vascularity Estimation by Arterial Spin Label Perfusion MRI—A Preoperative Tool for Patient Prognostication - Rai, Nidhi; Jamwal, Rupi; Singh, Bhanu Pratap; Gupta, Jyoti; Shankar, K. B.; Zaheer, Sufiyan (Indian Journal of Neurosurgery, 2023)
Introduction Brain tumors remain a significant cause of morbidity and mortality around the globe. Preoperative estimation of tumor vascularity is of great significance for a neurosurgeon. Aim of our study was to correlate tumor blood flow (TBF) using arterial spin labeling perfusion imaging (ASL-PI) with microvessel density (MVD), tumor grade, and preoperative prognostication of brain tumors.Materials and Methods This was a prospective observational cross-sectional study conducted in 63 patients of primary brain tumors already referred for magnetic resonance imaging. Absolute and relative mean and maximum TBF were calculated using ASL-PI and correlated with tumor grade and MVD at 10x and 40x magnificantion; thereby stydying the role of ASL-PI in brain tumor prognostication.Results The mean of maxTBF values (mL/min/100 g) in the gliomas group, meningiomas group, schwannoma group, craniopharyngioma group, and hemangioblastoma group was 147.15, 251.55, 96.43, 43.3, and 578.3, respectively. The median of maxTBF value in the gliomas group, meningiomas group, schwannoma group, craniopharyngioma group, and hemangioblastoma group was 131.5, 158.63, 94.5, 43.4, and 578.3, respectively.Discussion Significant correlation between meanTBF and MVD at 10X magnification (p-value < 0.001, rho =0.88) and a positive correlation between meanTBF and MVD at 40X magnification (p-value < 0.001) were seen. Significant correlation was also seen between maxTBF and MVD at 10X magnification (p-value < 0.001, rho = 0.91) and between maxTBF and MVD at 40X magnification. TBF in case of the hemangioblastoma was higher than other types of brain tumors (gliomas, meningiomas, and schwannomas). HighTBF value was seen in high-grade gliomas compared with low-grade gliomas with worse prognosis. TBF was high in typical meningiomas whereas low in atypical meningioma.Conclusion TBF by ASL-PI can be considered a noninvasive in vivo marker in predicting the grade of brain tumors and further assist in envisaging prognosis of the patients with brain tumors.
Keywords: Arterial spin labelled perfusion imaging (ASL-PI); brain tumors; preoperative prognostication; tumor blood flow (TBF) estimation; tumor microvessel density